Efficacy of Various Biocides Against Biofilm Bacteria Isolated from Cooling Waters of a Petrochemical Industry - Ozdemir, G.; Ceyhan, N. (Asian Journal of Chemistry, 2010)
Cooling water is essential in many industries, including power generation, chemical manufacture and petroleum refineries. Microbial fouling, the formation of biofilms in cooling water systems can lead to reduced heat transfer in condensers and heat exchangers. In order to prevent biofilms from creating these problems, a number of biocides are being used. In this study, the minimal inhibition concentrations (MIC) against 18 biofilm bacteria (8 g-negative and 10 g-positive), isolated at different times from cooling waters of a petrochemical industry, with increasing amounts (4-64 ppm) of 10-different biocides were investigated. The experiments were carried out at pH 7.9 and at 30 ºC. Henkel P3 Ferrocid 8583 and Concorde chem Hydrobio 620 exhibited the greatest antimicrobial effect against isolated biofilm bacteria. In addition, the reduction of the numbers of viable microorganisms count in the samples taking from cooling solution by selected biocides is determined. Interes-tingly, the results of this study clearly demonstrate that the most effective biocides against isolated bacteria did not have the same level when they were tried with cooling solution.